School trip photomarathons: engaging primary school visitors using a topic focused photo competition - Lindsey Braidley; Alice White; Richard Joiner; Trevor Collins (Association for Learning Technology, 2011)
The aim of this study was to explore the potential of photomarathons as a fun and engaging way to support students making connections between what they learn during a museum visit and what they learn in school or other contexts. Sixty primary school pupils aged between six and eleven took part in a photomarathon activity during their trip to the Roman Baths. The children were split into three groups. During their visit each group undertook three one-hour activities, namely: a photomarathon, a hands-on artefact exploration activity with a museum education officer, and a school-group handheld audio tour. For the photomarathon activity the children worked in subgroups of three and, for 15-20 minutes, took photos on three themes around the museum. At the end of the available time the children submitted a set of photos, one photo for each theme. Photo galleries for each theme were then generated and made available on a website for the pupils. The students voted for the best photo in each theme gallery, and a small prize was awarded to the members of each team that took the winning photo. A week after the visit the children were asked a number of questions concerning their visit. The photomarathon was spontaneously mentioned by 41% (23/56) of the children as the best activity in their visit to the Roman Baths, which was more than any other activity they engaged in during the visit. Overall, of the three activities the children liked the photomarathon the best. There were no age differences in how engaging the children found the photomarathon activity and all children regardless of age were able to take photographs.